Water-salt transport characteristics of saline soil under hydraulic remediation measures in the Yellow River Delta region of China - Li, Kesheng; Liu, Chuanxiao; Kong, Weihang; Geng, Yuhan; Xu, Wenshuo (International Journal of Agricultural and Biological Engineering, 2024)
To understand the water-salt transport process of saline soils in the Yellow River Delta region under traditional hydraulic remediation measures and to determine its engineering parameters, in this study, laboratory investigations were made to measure the soil salt content using three remediation practices under simulated rainfall conditions. The results indicated that under the rainfall intensity of 100 mm/h, 6-8 h are needed when the soil salt content tends to be constant. The distribution of the salt content presents a typically symmetrical shape regardless of the position of the saline soil relative to the concealed pipe, the open ditch, and the vertical shaft. The two-parameter exponential function indicates the relationship between the soil desalination rate and the horizontal distance from the pipe, the ditch or the shaft. The maximum spacing to build the salt drainage engineering of the concealed pipe, the open ditch or the vertical shaft in the laboratory is 4.79 m, 2.88 m, and 2.19 m, respectively. The effectiveness of salt drainage for coastal saline soils can be ranked from largest to smallest as the concealed pipe, the open ditch and the vertical shaft. The findings provide an experimental basis and reference for the application of hydraulic measures to remediate saline soils in this region.Keywords: water-salt transport, hydraulic measures, saline soil, Yellow River DeltaDOI: 10.25165/j.ijabe.20241705.8581Citation: Li K S, Liu C X, Kong WvH, Geng Y H, Xu W S. Water-salt transport characteristics of saline soil under hydraulic remediation measures in the Yellow River Delta region of China. Int J Agric & Biol Eng, 2024; 17(5): 193-199.